Axial‐field eddy‐current coupling: a 3D test problem for numerical experiments. (19th January 2017) - Fontchastagner, Julien; Lubin, Thierry; Netter, Denis
Abstract: This paper deals with a device which is particularly relevant to test 3D quasi‐static magnetic numerical computations: axial eddy‐current coupling. The authors have performed several numerical finite element method computations for this particular device. The eddy currents problem is solved thanks to 2 classical formulations based on magnetic vector and scalar potentials. Results are compared with experimental measurements made on a magnetic transmission already designed and built.